2000
DOI: 10.1128/mcb.20.5.1797-1815.2000
|View full text |Cite
|
Sign up to set email alerts
|

Arrest of G1-S Progression by the p53-Inducible Gene PC3 Is Rb Dependent and Relies on the Inhibition of Cyclin D1 Transcription

Abstract: The p53-inducible gene PC3 (TIS21, BTG2) is endowed with antiproliferative activity. Here we report that expression of PC3 in cycling cells induced accumulation of hypophosphorylated, growth-inhibitory forms of pRb and led to G 1 arrest. This latter was not observed in cells with genetic disruption of the Rb gene, indicating that the PC3-mediated G 1 arrest was Rb dependent. Furthermore, (i) the arrest of G 1 -S transition exerted by PC3 was completely rescued by coexpression of cyclin D1 but not by that of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(229 citation statements)
references
References 116 publications
(139 reference statements)
12
216
1
Order By: Relevance
“…Btg2 belongs to the BTG/Tob family which in mammals comprises six proteins that regulate cell cycle progression (Winkler, 2010). BTG2 controls G1 to S phase progression 18 negatively by direct inhibition of cyclin D1 transcription (Guardavaccaro et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Btg2 belongs to the BTG/Tob family which in mammals comprises six proteins that regulate cell cycle progression (Winkler, 2010). BTG2 controls G1 to S phase progression 18 negatively by direct inhibition of cyclin D1 transcription (Guardavaccaro et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Btg proteins exert cellular functions by interacting with transcriptional coactivators or corepressors, hence modulating their transcriptional activities (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). For example, it has been found that Btg2 impairs G1-S cell cyclephase progression by inhibiting cyclin D1 transcription (Guardavaccaro et al, 2000), that it can associate with HoxB9 (Prevot et al, 2000), and BMPregulated Smad1 and 8 (Park et al, 2004) to promote their transcriptional activity, and that it can enhance Math1 promoter activity (Canzoniere et al, 2004). Similarly, Btg1 has been shown to interact with and stimulate the activity of transcription factors that positively regulate myogenic processes, in particular myogenic factors such as MyoD, all-trans retinoic acid receptors, and the T3 receptor TR␣1 (Busson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different model systems suggest that they act as antiproliferative genes, they can promote cell differentiation and also regulate apoptosis and cellular senescence (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). Btg/Tob genes encode for a group of structurally related proteins, characterized by the presence of two novel and highly conserved domains ("antiproliferative" boxes A and B) located in the first 120 residues of the protein (Guehenneux et al, 1997;Guardavaccaro et al, 2000). This gene family is conserved across phylogeny, with two members identified in invertebrates: the gene Fog-3 in C. elegans (Chen et al, 2000) and the mRNA with accession number AF177464 in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…The BBB can also act in an inhibitory mode by expression of osteonectin, a glycoprotein that has been shown to inhibit angiogenesis by binding vascular endothelial growth factor, 16 and PC3, an antiproliferative protein induced by the p53 protein. 17 The BBB is also rich in expression of molecular transporters and proteins involved in cellular trafficking. The differentially expressed transport systems that were identified in these studies facilitate organic anion transport (oatp2), sodium and potassium transport (Naϩ,Kϩ ATPase), energy substrate transport in the form of lactic acid and ketone bodies [monocarboxylate transporter (MCT1)], amino acid transport [cationic amino acid transporter (CAT1)], and protein transport [transferrin receptor (TfR)].…”
Section: Figmentioning
confidence: 99%